Longitudinal volumetric analysis of in ovo compartments in chicken eggs using ultra-high-field magnetic resonance imaging - Streckenbach, Felix; Schön, Hanna; König, Julia; Frank, Marcus; Langner, Inga; Stachs, Oliver; Jonitz-Heincke, Anika; Langner, Sönke; Lindner, Tobias; Schätzel, Jana (Frontiers in Veterinary Science, 2024)
IntroductionThe chicken egg, with its in ovo compartments, is a widely used and popular animal model in experimental studies. This study aimed to quantify the volumes of the yolk/yolk sac, amniotic fluid, and chicken embryo in ovo using non-invasive ultra-high-field magnetic resonance imaging (UHF-MRI).Materials and methodsIn total, 64 chicken eggs were examined using a 7 T UHF-MRI scanner, acquiring T2-weighted anatomical images of the entire egg from developmental day 1 to 16 (D1-D16). Four eggs were scanned each developmental day, and the volumes of the yolk/yolk sac, amniotic fluid, and embryo were quantitatively assessed.ResultsUHF-MRI facilitated the in ovo quantitative assessment of the yolk/yolk sac starting from D1 and the embryo from D5 onward. The yolk/yolk sac volume increased from D1 to D6 before progressively decreasing until D14. The amniotic cavity could be detected on D6, with its fluid volume increasing steadily until D14. The embryo’s volume increased consistently throughout the developmental period, reaching its peak at D16.DiscussionUHF-MRI allows in vivo assessment of embryonic development, providing non-invasive, longitudinal insights into the volumes of the yolk/yolk sac, amniotic fluid, and chicken embryo. The investigation method described in this study may provide a standardized model for biomedical research in the developing chicken embryo, supporting various experimental applications.